Structural and Magnetic Properties of Pr0.7Bi0.3Mn1−xFexO3 (0 ≤ x ≤ 0.2) Manganites Oxides Prepared by Sol-gel Method - Kh. Sbissi; D. Fatnassi; M. Ellouze; E. K. Hlil; F. Elhalouani (Jordan Journal of Physics, 2025)
The morphology, structural and magnetic properties of Pr0.7Bi0.3Mn1-xFexO3 manganites oxides, prepared by sol-gel method, have been investigated to study the effect of the substitution of Mn by Fe. X-ray powder diffraction, Scanning Electron Microscopy (SEM), Fourier transforms infrared spectroscopy (FT-IR) and magnetic measurements for the systems have been investigated. Rietveld analysis of the X-ray powder diffraction show that the samples crystallize in the orthorhombic perovskite system with Pnma space group. The average particle size of about 60 nm was obtained from X-ray diffraction. We have found that with increasing x doping concentration of Fe, the unit cell volume decreases. Magnetic measurements versus temperature with an applied magnetic field of 0.05T show that all samples exhibit antiferromagnetic to paramagnetic transition with increasing temperature, at Neel temperature. Keywords: Sol-gel; Manganites; Perovskite; Magnetic properties; Rietveld analysis.